Strengthening the regulation regimes for collecting societies in South Africa and Nigeria: any room for competition law? - Oriakhogba, Desmond Osaretin (Department of Commercial Law, 2019)
Collective management organisations (CMOs), also know as collecting societies, are natural monopolies and they occupy dominant positions, with anticompetitive tendencies if not regulated, in the copyright management and licensing market. Regulation regimes must thus set efficiency, transparency and accountability standards for CMOs. In achieving these standards, competition law aims to address specific concerns through the regulation of CMOs’ capacity to limit copyright owners’ economic rights, discriminate against them in terms of membership, and fix excessive and discriminatory royalty rates for users. CMOs in Nigeria and South Africa are subject to copyright-sector specific regulation. Nigeria and South Africa have competition legislations, which applies in principle, but has so far not been applied to CMOs in practice. Undertaken as desk and library based study, the thesis examines the regulation of CMOs in Nigeria and South Africa. It determines if the regulation in both countries empower the relevant copyright regulatory agency to address the competition-related concerns in regards to CMOs and whether there is need to apply competition law to CMOs in both countries. The thesis explores the copyright and competition law interface. It argues that, although adopting different methodologies, both fields pursue the similar goal of promoting creativity by enhancing dynamic competition in copyright markets which underscores the regulation of CMOs. It concludes that whereas competition law does not need to be applied to CMOs in Nigeria, there is need to apply it to CMOs in South Africa because unlike its Nigerian counterpart, there are observable gaps in the South African copyright regime in the treatment of the competition-related concerns of CMOs. At the time of writing this thesis, both Nigeria and South Africa are reviewing their copyright legislation. CMOs regulation is a major issue being considered in the process. The thesis will be indispensable, the author hopes, in determining the form and content of CMOs regulation in both countries. Further, there is scarcity of literature in Nigeria and South Africa on the copyright and competition law interface relating to CMOs regulation. The thesis will fill this gap and form an invaluable resource for further research; a useful guide for copyright and competition law regulators and enforcers; and a rich reference material for academics, judges and policy makers in Nigeria and South Africa.